Indole primes plant defense against necrotrophic fungal pathogen infection - Shen, Qinqin (PLoS One, 2018)
Indole is a volatile compound and emitted from plants challenged by insect infestation or mechanic wounding. It has been shown to prime defense against herbivory. Here we identified that indole induced defense either directly or as a priming agent against necrotrophic pathogens Fusarium graminearum and F. moniliforme in maize and Magnaporthe oryzae in rice. With indole pretreatment, smaller lesions were developed in infected leaves, as well as less fungal growth. Indole induced H(2)O(2) burst in the priming stage like other priming substances did. Such priming relied on mitogen-activated protein kinase (MAPK) cascade, which potentially activated downstream defense signaling. In addition, indole priming resulted in earlier and stronger defensive gene expression upon pathogen infection, including genes of jasmonate and phytoalexin biosynthesis, pathogenesis-related proteins (PRs) and anti-oxidant enzymes, which enhanced plant resistance. Meanwhile, H(2)O(2) was also identified as the priming agent to induce plant defense. Taken together, indole exhibited priming function not only against herbivory but also necrotrophic pathogens. The common emission of indole in plants suggests that it plays important roles as the universal and endogenous priming substance in plant defense.